Kinematics Analysis and Verification of 3DOF-4RRRR⊥ Redundant Parallel Drive Platform - Shaoxiong Zhang; Qiguang Li; Lingtao Liu; Yao Luo; Wenqiang Yue (Jixie chuandong)
In order to solve the problem of limited operation range of medical surgical instrument arm， a three-degree-of-freedom surgical instrument arm platform based on 4RRRR⊥ symmetrical orthogonal parallel link manipulator is proposed. The kinematic equation of the platform is derived using the vector closed loop method， and the workspace of the platform is analyzed and calculated by using the numerical search method according to the position constraints of each bar. On this basis， the numerical simulation of the forward and inverse kinematics of the platform is completed by using Matlab， and the numerical example of the forward solution shows that the error accuracy can reach the order of 10-8. At the same time， the inverse kinematics of the platform is further simulated by Adams to verify its correctness. Experiments are carried out on a prototype， and the experimental data shows that the position error of the platform controlled by the kinematic equation of the platform is ±1 mm and the attitude error is ±1°. Simulations and experiments show that the mechanism driven by the parallel manipulator， as the position adjustment platform of the surgical instrument arm， can effectively expand the dynamic adjustment range of the operating space of the surgical instrument arm. The kinematics equation also provides an important reference for the follow-up dynamic control method of this kind of redundant parallel mechanism.